Antecedents of customer satisfaction in the higher education institutions of South Africa - Jager, Johan W de; Jan, Muhammad Tahir (Business Perspectives, 2015)
Higher education institutions like most other organisations have realized the importance of customer- centred approach to survive amongst competitors. This is very important keeping in mind the globalisation of higher education and consequent competition. The primary objective of the study is to determine the impact of different variables on customer satisfaction in the higher education sector. More explicitly, this study has the following aims; to identify the effect of support facilities and infrastructure on customer satisfaction; to ascertain the effect of location and access on customer satisfaction and to determine the effect of image and marketing on customer satisfaction. A random sample of three hundred and ninety-one students was chosen. A review of the structural model indicates that only one hypothesis can be supported statistically, i.e., the causal link from support facilities and infrastructure to customer satisfaction.